Anatomical and functional mapping of striatal circuits controlling licking - Mutlu, Sevinç (2016)
The basal ganglia receive information about sensory-motor state, internal state, the recent history of actions and their outcomes. They integrate information in order to select the optimal action in the right sensory environment, to receive or avoid the predicted outcome based on the recent history. Eventhough models, such as reinforcement learning, reward prediction error, direct and indirect pathway antagonism, linking cognitive-behavioral phenomenon with neural data are widely agreed upon, they are not sufficient to explain a vast amount of experimental data. Therefore the roles of basal ganglia structures in action selection are yet to be understood. Striatum is considered to be the main basal ganglia structure that receives input from the whole cortex, many thalamic nuclei and midbrain dopaminergic cells and integrates these inputs and projects onto basal ganglia output structures. Therefore, striatum could be the key structure involved in optimal action selection by integrating information from different brain structures, together with dopaminergic input and where the decision for optimal action is made. Therefore understanding the role of striatum in action selection could be the key step in understanding basal ganglia functioning. (…)